Prognostic Load Balancing Strategy for Latency reduction in Mobile Cloud Computing - Cheema, Ibrahim A.; Ahmad, Mudassar; Jan, Fahad; Bin Ngadi, Dr. Asri (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
In Mobile Cloud Computing (MCC), load balancing is essential to distribute the local workload evenly across all the nodes either statically or dynamically. A high level of user satisfaction and resource utilization ratio can be achieved by ensuring an efficient and fair allocation of all computing resources. In the absence of proper load balancing strategy/technique the growth of MCC will never go as per predictions. The appropriate load balancing helps in minimizing resource consumption, implementing fail-over, enabling scalability, avoiding bottlenecks. In this paper, a prognostic load balancing strategy is proposed and implemented for computational latency reduction in MCC. Also the results of proposed technique is compared with existing techniques. Finally this study concludes that the proposed predictive technique reduces associated overheads, service response time and improves performance. There are also Various parameters that are identified and used to compare the existing techniques.Â Â 